2018
DOI: 10.1111/1751-2980.12589
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features of advanced colorectal serrated lesions: A single‐center study in China

Abstract: ASLs are more likely to occur in the proximal colon, and mainly present as flat and sub-pedunculated types. Large ASLs are significantly associated with sACN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
1
3
1
Order By: Relevance
“…In analysis of endoscopic and pathological factors associated with dysplasia/carcinoma, distal colon, large size, polypoid morphology, surface-changes, no mucus cap, adenomatous surface-patterns, and histologically complete resection was significantly associated with SSLs with dysplasia/carcinoma, particularly large size, depression and NICE type 2/3 in multivariate analysis. Similar to previous studies [8,[17][18][19][20]33,[35][36][37][38][39], SSLs with dysplasia/carcinoma occurred more frequently in the proximal colon than in distal colon (52/254 [20.5%] vs. 23/254 [9.1%]) compared with SSLs without dysplasia. However, the risk of dysplasia was signifi-cantly higher in the distal colon than in the proximal colon (23/54 [42.6%] vs. 52/200 [26.0%], p = 0.02).…”
Section: Discussionsupporting
confidence: 88%
“…In analysis of endoscopic and pathological factors associated with dysplasia/carcinoma, distal colon, large size, polypoid morphology, surface-changes, no mucus cap, adenomatous surface-patterns, and histologically complete resection was significantly associated with SSLs with dysplasia/carcinoma, particularly large size, depression and NICE type 2/3 in multivariate analysis. Similar to previous studies [8,[17][18][19][20]33,[35][36][37][38][39], SSLs with dysplasia/carcinoma occurred more frequently in the proximal colon than in distal colon (52/254 [20.5%] vs. 23/254 [9.1%]) compared with SSLs without dysplasia. However, the risk of dysplasia was signifi-cantly higher in the distal colon than in the proximal colon (23/54 [42.6%] vs. 52/200 [26.0%], p = 0.02).…”
Section: Discussionsupporting
confidence: 88%
“…The trend toward increased prevalence of RSCC is probably a consequence of better screening. Although the present study found that there were more malignancies in the left‐sided colon and rectum, our previous research showed that advanced serrated lesions, a type of precancerous lesions, were more likely to occur in the right‐sided colon …”
Section: Discussioncontrasting
confidence: 85%
“…Although the present study found that there were more malignancies in the left-sided colon and rectum, our previous research showed that advanced serrated lesions, a type of precancerous lesions, were more likely to occur in the right-sided colon. 37 The rightward shift of CRC was first reported by Ottenheimer et al 38 in 1955. We also reviewed and summarized some related studies from recent decades ( Table 5).…”
Section: Discussionmentioning
confidence: 85%
“…Serrated neoplasia appears to be a universal human phenomenon; SSLs and other serrated lesions are found in many disparate populations and ethnic groups. Although most epidemiology studies of SSLs were performed in the United States or Europe, serrated polyps have been reported worldwide, in studies from Korea, 57 Japan, 58,59 China, 60,61 Australia, 62 Peru, 63 Argentina, 64 Russia, 65 Turkey, 66 India, 67 and Nigeria, 68 among other countries. In general, countries that do not screen the population for CRC, or that perform colonoscopies primarily for diagnostic purposes, report lower prevalence values for adenomatous polyps and serrated polyps.…”
Section: Epidemiologymentioning
confidence: 99%